The Effect of Iron Dextran Injection on Daily Weight Gain and Haemoglobin Values in Whole Milk Fed Calves - Jennifer Allan; Peter Plate; Steven Van Winden (Animals, 2020)
Anaemia caused by iron deficiency has long been reported in dairy calves. This study investigated iron deficiency anaemia on UK dairy farms feeding whole milk and evaluated the effect of iron supplementation on the daily weight gain (DG) and haemoglobin (Hb) levels of these calves. Two-hundred-and-thirty-seven calves were enrolled across six farms. At enrolment, calves were randomly allocated to either receive treatment with iron injection (INJ; n = 120) consisting of 5 mL (1 g iron) of iron dextran (Uniferon 20% Injection, Pharmacosmos) or no injection, control (CON; n = 117). Calves were blood-sampled for Hb and total proteins and weighed at weeks one, six and 12 of age. Iron had a significant effect on DG from one to six weeks, with an average 78 g/d (SD 18 g/d, n = 188, 95% Confidence interval: 44–112 g/d, p < 0.001) DG increase in the INJ calves. Iron had a significant effect on Hb concentration at six weeks between the INJ group and CON group (110.7 (SD 12.4) versus 94.9 g/L (SD 13.2), respectively). Calves with a higher growth rate from one to six weeks were more likely to have low Hb levels at six weeks. There was farm variation in both Hb levels and DG, however, despite this, there was an effect of iron across all farms.